The art of the Hekatompedon inscription and the birth of the stoikhedon style - Butz, Patricia A. (Monumenta Graeca et Romana, 2010)
The purpose of this book is to present the Hekatompedon Inscription at Athens ( IG I³ 4) as a major monument of Greek art, legitimately on a par with more famous landmarks of the Greek aesthetic tradition like the Parthenon Frieze. Inscribed most probably in the middle of the decade that saw the Greek response to the Persian invasion, the Hekatompedon Inscription has long been recognized for its historical and religious importance. This study looks at the inscription on its own terms: the unique fusion of its visual and textual content in that most Greek of epigraphical layouts, the stoikhedon style. Such an approach leads to the question of origins: where and why was the stoikhedon style formulated and where does the Hekatompedon Inscription stand in that development? Egypt's influential system of proportions and use of grids will be considered determinative for the very first time.